Effect of g‐C3N4 nanofiller as filler on mechanical properties of multidirectional glass fiber epoxy hybrid composites. Issue 9 (21st August 2019) - Naidu, P. Pratap; Raghavendra, Gujjala; Ojha, Shakuntala; Paplal, Banoth
ABSTRACT: An experimental study was carried out to investigate the flexural strength of glass‐fiber‐reinforced (multidirectional woven glass fiber) epoxy hybrid composites filled with different proportions (1, 1.5, 2, 2.5, and 3%) of graphitic carbon nitride (g‐C3 N4 ) filler. g‐C3 N4 powder filled glass epoxy composites were fabricated in conventional hand lay‐up method. Results showed an increase in flexural strength of g‐C3 N4 particles content by 2% and beyond which the strength decreased. With the addition of 2 wt % of g‐C3 N4 in glass‐fiber‐reinforced epoxy composites, the tensile strength increased by 11% and the flexural strength increased by 13%. The eroded surface of the specimen was observed under scanning electron microscope and the results are reported. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48413. Abstract :